CREATIVE COMPETENCE IN THE EDUCATIONAL PROCESS PEDAGOGICAL TECHNOLOGIES IN FORMATION - Akhmedova Nigora Dadakhonovna (Journals Park Publishing, 2022)
This article talks about pedagogical technologies in the formation of creative competence in the process of education. It is known to achieve high efficiency in teaching it depends on the choice of teaching methods educational technologies, suitable for the types, forms and educational content of lessons and how to use them.
Keywords: pedagogical process, pedagogical etiquette, ethics